2005
DOI: 10.1007/s10803-005-3296-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Children with Autistic Spectrum Disorders Served in Comprehensive Community-based Mental Health Settings

Abstract: This study describes the characteristics of children with autistic spectrum disorders (ASD) receiving treatment in community mental health settings. Data from a national community mental health initiative was used to identify children who had received a primary diagnosis of ASD. These children were compared with children with other diagnoses on socio-demographic and psychosocial characteristics, presenting problems and service histories. Regardless of diagnosis, children were most often referred to service bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
52
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 29 publications
7
52
1
Order By: Relevance
“…The gender percentage reproduces the ratio of four boys to one girl found in autism prevalence studies (Hill;Zuckerman;Fombonne, 2014) and in previously cited studies of US services (Mandell et al, 2005;Brookman-Frazee;Taylor;Garland, 2010). The majority (64%) of autistics is in the 10 to 19 age group, with a much smaller number of young children in the services.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The gender percentage reproduces the ratio of four boys to one girl found in autism prevalence studies (Hill;Zuckerman;Fombonne, 2014) and in previously cited studies of US services (Mandell et al, 2005;Brookman-Frazee;Taylor;Garland, 2010). The majority (64%) of autistics is in the 10 to 19 age group, with a much smaller number of young children in the services.…”
Section: Discussionsupporting
confidence: 79%
“…As for psychosocial data, like the US study cited (Mandell et al, 2005), few patients do not live with their families/caregivers. This indicates that only a minority of this population resides in shelters in the Rio de Janeiro metropolitan area, which does not mean that the services should neglect mapping and interacting with institutional sheltering organizations in their regions, aiming to overcome existing modes of exclusion and segregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,22 Other studies also have found rural/urban 23 and ethnic differences in ASD identification. 24,25 Little is known, however, about how child characteristics and local resources influence medication treatment; therefore, in addition to estimating the prevalence of psychotropic medication use among children with ASDs, we explored the relative contributions of child, county, and state characteristics to its use. Child Characteristics-Demographic characteristics, including age, race/ethnicity, gender, and county of residence, were abstracted from the Medicaid eligibility file.…”
mentioning
confidence: 99%
“…We hypothesized that the diagnoses children received prior to receiving a diagnosis of autism once they entered specialty care-especially given that parents of children with autism and those of children with other disorders often present for treatment with the same complaints (Mandell, Walrath, Manteuffel, Sgro, & Pinto-Martin, 2005b)-might provide insight into clinicians' thought processes and family behavior that lead to delayed diagnosis. The goal of this study therefore was to determine, among a sample of Medicaid-eligible children, the extent to which children ultimately diagnosed with autism were first diagnosed with other disorders and whether those diagnoses differ by ethnicity.…”
mentioning
confidence: 99%